Memaknai Unsur Naratif Dalam Film Parasite Melalui Perspektif Filsafat Kebebasan Manusia - Rifqi Nadhmy Dhia; Firman Kurniawan (Universitas Multimedia Nusantara, 2021)
Human beings essentially have social freedom inherent in themselves. Parasite (2019), a film which raises social issues in South Korea, has a close relationship with the reality of social stratification in society. Using the film Parasite as a case study, this article attempts to trace the tendency of meaning production regarding the philosophy of human freedom. In the process, this article draws the conclusion that the depiction of a person within the social structure in the narrative element of the Parasite film can represent the meaning of social freedom which is also limited by other human freedoms. Keywords: Communication; Philosophy; Social Freedom; Social Structure; Parasite